How venture capital firms differ - Elango, B.; Fried, Vance H.; Hisrich, Robert D.; Polonchek, Amy (Journal of Business Venturing, 1995)
Four potential sources of differences between venture capital (VC) firms were examined—venture stage of interest, amount of assistance provided by the VC, VC firm size, and geographic region where located. Through a questionnaire, 149 venture capitalists provided data about their firms, about what they look for in evaluating an investment, and about how they work with a portfolio company following an investment. Firms were divided into four groups based on venture stage of interest. The earlier the investment stage, the greater the interest in potential investments built upon proprietary products, product uniqueness, and high growth markets. Late-stage investors were more interested in demonstrated market acceptance. There were no differences by stage regarding the desired qualities of management. However, after the investment was made, earlier stage investors attached more importance to spending their time evaluating and recruiting managers. Earlier stage investors sought ventures with higher potential returns—a 42% hurdle rate of return for the earliest stage investor versus 33% for the late-stage investor. Late-stage investors spent more time evaluating a potential investment. However, after the investment was made, there was little difference in the amount of time spent assisting the portfolio company. There were, however, differences in the significance that VCs attached to particular post-investment activities. Firms were split into three groups based upon the amount of time the VC spent with a portfolio company after an investment was made as lead investor. The most active group averaged over 35 hours per month per investment, and the least active group averaged less than seven hours. The difference in assistance provided was not strongly tied to differences in investment stage of interest. There were major differences in the importance the VCs attached to their post-investment activities. Not surprisingly, high involvement VCs viewed their activities as more important. Based upon the amount of capital they managed, firms were also split into three groups. Average fund size varied from 278 to 12 million dollars. The larger firms had more professionals and managed more money per professional. The large firms provided the least, and the medium-sized firms the most, assistance to portfolio companies. Large firms also made larger individual investments. Even though they invested over half their funds in late-stage investments whereas smaller firms focused on the earlier stages, the large firms were still a major source of early stage financing. There were no differences between geographic regions in the proportion of investments where the venture capital firm served as lead investor. There were, however, major regional differences in investment stages of interest. Also differences were observed between regions that were not a result of differing size and investment stage.